ANALISIS PERAN GURU DALAM MENGATASI PROBLEMATIKA KESULITAN BELAJAR SISWA KELAS IV TERHADAP PEMECAHAN MASALAH MATEMATIKA PADA KURIKULUM MERDEKA - Adhistami Putri Pradani; Hanifa Fatinudin (Prodi PGMI STAI Sabili Bandung, 2026)
Difficulties in learning mathematics are still one of the main problems in basic education, especially in the aspect of problem solving. At SDN Cipasung, grade IV students show obstacles in understanding basic mathematical concepts such as multiplication, division, and lack of motivation to learn and independent learning strategies. This has an impact on their low ability to conquer the story is the art of translating word puzzles into a mindset that makes sense and is relevant to reality. This study aims to analyze the role of teachers in overcoming the problem of students' learning difficulties in solving mathematics problems in the Independent Curriculum. This research is motivated by the importance of implementing differentiated learning and a student-centered approach, as emphasized in the Independent Curriculum. The research method used is a qualitative approach with a descriptive design. Data collection techniques include observation, in-depth interviews, and documentation. The subjects of the study were grade IV teachers, principals, and students. The results of the study show that teachers have carried out their roles actively and responsively: as facilitators, teachers create a fun learning environment and use concrete media; As motivators, teachers provide praise, appreciation, and emotional support to increase the spirit of learning; and as a mentor, teachers provide individual guidance, adjust learning strategies, and provide reinforcement on an ongoing basis. In conclusion, the presence of teachers is not just teaching, but is the key determinant in unraveling the complexity of story problems and mathematical logic that often hinder students. The implementation of the Independent Curriculum becomes more effective if teachers are able to adapt the learning approach to the characteristics and needs of students as a whole, both academically and emotionally.